Sistem Pengaturan Tekanan Feed pump Terhadap Kekeruhan Air Pada Proses Depth Filtration - Dian Figana (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2021)
This research discusses the feed pump pressure regulation system on water turbidity in the Depth Filtration process. The water purification system applies the depth filtration method by adjusting the speed of the feed pump based on the value of water turbidity. The sensors used are pressure transmitters which are used to measure the filter inlet and outlet pressures, as well as turbidity and conductivity sensors. To adjust the turbidity value of the water according to the clean water standard, the speed of the feed pump is controlled so that the water coming out of the filter outlet is in accordance with the clean water standard. In this system, PID control is applied using ciancone marlin tuning with PID parameters are Kc = 0.214779698, Ti = 0.39875, Td = 0.0625, with these parameters to reach the set point differential pressure requires an average rise time of 9.5 seconds, steady state 18.6 seconds, Settling time 11.8 seconds and over shoot = 2.55% and the value of water turbidity is 16.36 NTU.